Application of the UTAUT (Unified Theory of Acceptance and Use of Technology) Model to Analyze the Acceptance Level of Using Zi.care at RSIJ (Jakarta Islamic Hospital) Cempaka Putih, Indonesia - Brigita Natalia Br Surbakti; Daniel Happy Putra; Puteri Fannya; Dina Sonia (HM Publisher, 2023)
Jakarta Islamic Hospital Cempaka Putih is a teaching hospital. Based on the results of observations, it was found that there were problems in implementing Zi.care at this hospital, where the system had been used but was temporarily stopped. Zi.care is a SIMRS and also an RME at RSIJ Cempaka Putih. The aim of using Zi.care is to make services effective and efficient, administration more informative and integrated, information that is real-time, integrated with BPJS, making online registration and telecommunications easier via Mobile App, and patients can manage their own medical records via Mobile App. This study aimed to evaluate Zi.care using the UTAUT method at RSIJ Cempaka Putih. This research uses a cross-sectional design with a quantitative approach to an analytical observational study to determine the relationship between causal factors and effect factors in the application of Zi.care. Sampling technique with proportionate stratified random sampling, namely sampling based on the number of divisions from each sub-population consisting of medical staff, doctors, pharmacists, laboratory assistants, radiologists, and nurses. The sample was 150 respondents who used Zi.care. The results of the normality test show that the data is abnormal because the p-value < 0.05, so the cut point taken is the median. Hypothesis testing is carried out using statistical calculations Chi-square with the help of software SPSS 24.0. The research results show that performance expectations, effort expectations, and social influence have a relationship with usage intention while facilitating conditions have no relationship with usage behavior.